2011
DOI: 10.1590/s0102-67202011000400007
|View full text |Cite
|
Sign up to set email alerts
|

Complicações e óbitos nas operações para tratar a obesidade mórbida

Abstract: -Background -Bariatric surgery, although complex, has low morbidity and mortality, but when they happen, serious consequences are expected in patients evolution. Aim -To evaluate the presence of complications and deaths in patients with morbid obesity who underwent surgical treatment. Methods -Retrospective analysis of 656 patients undergoing bariatric surgery. Were analyzed: sex, age, preoperative weight, body mass index before surgery, procedure performed, length of hospital stay, post-operative complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Obesity is characterized in patients whose body mass index (BMI) is >30 kg/m 2 . However, only patients with BMI ranging from 35-40 kg/m 2 (class II obesity) with comorbidities or BMI>40 kg/m 2 (class III obesity) are suitable candidates for bariatric surgery 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is characterized in patients whose body mass index (BMI) is >30 kg/m 2 . However, only patients with BMI ranging from 35-40 kg/m 2 (class II obesity) with comorbidities or BMI>40 kg/m 2 (class III obesity) are suitable candidates for bariatric surgery 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The operative mortality rate described in the literature ranges from 0.1 to 2%, depending on the procedure and characteristics of the patients 23 . Our mortality in bariatric surgery, in a previous publication, was 1.21% 30 . In this study there was no mortality, though.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 48%
“…In this study the complication rate was 28.99%, where 57.35% of them happened during the first postoperative year. Another study found inferior complication rate, 4.87% 20 . At the same time, the variables evaluated were distinct.…”
Section: Discussionmentioning
confidence: 94%